Transient Transformation of Red Algal Cells: Breakthrough Toward Genetic Transformation of Marine Crop Porphyra Species - Mikami, Koji; Hirata, Ryo; Takahashi, Megumu; Uji, Toshiki; Saga, Naotsune (IntechOpen, 2011)
None